From Outsiders to On-Paper Equals to Cultural Curiosities? The Trajectory of Diversity in the USA - John J. Betancur (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper examines the genesis and trajectory of diversity in the USA. It argues that unfortunately diversity was more a product of market interests and differential processes in the recruitment of workers at different times and for different purposes than a smooth process of incorporation of immigrant groups from different cultures and continents. At the end, diversity assumed a highly hierarchical form with blacks at the bottom and whites at the top within a framework of manifest destiny and inequality. Confronting an unequal status, non-whites engaged in group-based struggles that transformed them into political communities and the process into a social struggle. The paper concludes with a call for European countries to learn from this experience and try to preempt it by moving to incorporate newcomers in such a way that they become fully contributing members of the societies they enter within a mutually transforming process
Keywords: 330; Diversity; Race Relations; Racial Politics; Immigrants; Identity Formation